US Cyber Command warns of Confluence attacks. Issue 9 (September 2021) - Unknown
Abstract : US Cyber Command, which is responsible for the military cyber capabilities of the US, has taken the unusual step of issuing a warning to enterprises about ongoing attacks. These exploit a recently patched vulnerability in Atlassian's Confluence collaboration platform.